The Influence of Visual Merchandising and Discount Price on Impulsive Buying at H&M Store (H&M Store PVJ Bandung Case Study) - Suryaatmadja, Lambok; Sibarani, Mentiana (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
This research aims to determine the influence of visual merchandising and discount prices on impulsive buying at the H&M store Paris Van Java. This type of research is causal explanatory research. In this research, data is obtained through primary data and secondary data techniques. Primary data collection was carried out by distributing questionnaires, while secondary data collection was carried out in this research by literature study and data collection by looking at historical data from the past. This research used a minimum of 30 respondents calculated using the Marlina method by taking respondents as consumers of the H&M store Paris Van Java, respondents who had made unexpected purchases (impulsive buying), respondents with an age range of 18 – 68, and from all social classes. The data used is quantitative. The data collection technique uses a questionnaire. The research consists of two independent variables, namely visual merchandising (X1) and discount price (X2) and consists of one dependent variable (Y), namely impulsive buying, as well as, Next, analysis of the Structural Equation Model (SEM) is carried out using Smart -PLS 3.0. The results of this research show that the variables visual merchandising (X1) and discount price (X2) have a significant effect on impulsive buying (Y). They have a significant effect on purchasing decisions by 67% and the rest is influenced by other variables.